Solve the simultaneous equations: (1) y – 2x – 4 = 0 , (2) 4x^2 + y^2 + 20x = 0

Rearrange (1): y=2x+4

Subsitute this into (2): 4x2+(2x+4)2+20x=0

Simplify and collect like terms: 8x2+36x+16=0

Factorise: (2x+1)(x+4)=0

Therefore: 2x+1=0 -> x=-0.5  and x+4=0 -> x=-4

Substitute this into (1) to get values for y: y=3 and y=-4

Answered by Anastasia T. Maths tutor

3488 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the derivation of (sinx)(e^2x)


The probability distribution of the random variable X is given by the formula P(X = x) = 0.09+0.01x^2 for x= 1,2,3,4,5 ). Find E(X).


Differentiate with respect to x. y(x) = e^(7x^2)


What is the chain rule?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences